2017
DOI: 10.3389/fpls.2016.02075
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Hydraulic Safety Strategies in Three Co-occurring Anacardiaceae Tree Species in a Chinese Savanna

Abstract: Vulnerability segmentation, the condition under which plant leaves are more vulnerable to drought-induced cavitation than stems, may act as a “safety valve” to protect stems from hydraulic failure. Evergreen, winter-deciduous, and drought-deciduous tree species co-occur in tropical savannas, but there have been no direct studies on the role of vulnerability segmentation and stomatal regulation in maintaining hydraulic safety in trees with these three leaf phenologies. To this end, we selected three Anacardiace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 60 publications
3
40
0
Order By: Relevance
“…The relationship between hydraulic segmentation and the degree of isohydricity has been rarely examined. In the study of Pivovaroff et al (), no clear pattern between daily range of leaf water potential and HSM HS was observed, but Zhang et al () reported positive safety margins in more isohydric species. In the current study, hydraulic vulnerability was less variable in leaves than stems, which may be due to the notion that leaf hydraulic traits, including embolism resistance, may be responsive to growth conditions (Blackman et al, ; Johnson et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The relationship between hydraulic segmentation and the degree of isohydricity has been rarely examined. In the study of Pivovaroff et al (), no clear pattern between daily range of leaf water potential and HSM HS was observed, but Zhang et al () reported positive safety margins in more isohydric species. In the current study, hydraulic vulnerability was less variable in leaves than stems, which may be due to the notion that leaf hydraulic traits, including embolism resistance, may be responsive to growth conditions (Blackman et al, ; Johnson et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…These hydraulic traits characterizing plant vulnerability to embolism are often well correlated with climatic factors across species, therefore informing the evolutionary drivers shaping the adaptation of drought response strategies (Blackman et al, ; Bourne, Creek, Peters, Ellsworth, & Choat, ; Choat et al, ; Li, Blackman, Choat, et al, ; Skelton et al, ; Trueba et al, ). In addition, significant differences between leaf and stem vulnerability provide evidence for hydraulic vulnerability segmentation (HSM HS ), a strategy that minimizes water loss during drought via leaf shedding (Pivovaroff, Sack, & Santiago, ; Zhang, Zhang, & Cao, ; Zhu, Liu, Xu, Cao, & Ye, ). Given their functional significance, examining how different metrics are related to these key drought tolerance traits will advance our understanding on species life‐history strategies, as well as helping to identify species at risk of drought mortality and clarifying the underlying mechanisms providing drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the mortality hypothesis presented in the present study may not translate to larger trees. For example, drought-induced crown dieback in larger trees often occurs at the periphery of the tree crown (Rood et al 2000;Sperry et al 2002;Zhang et al 2017), rather than sequential senescence observed in the current study, where older leaves senesce first to supply nutrients to younger leaves and shoots (Munné-Bosch and Alegre 2004). As low-intensity fires typically scorch tree crowns from the bottom up, senescing foliage at the periphery of a large tree crown may not provide the post-fire recovery advantage hypothesised for saplings.…”
Section: Future Research Needsmentioning
confidence: 71%
“…With regard to plant water relations, the trade‐off between hydraulic safety (P 50 ) and efficiency (K s ) has been intensively studied. Although this trade‐off has been observed in many studies (Bourne et al, ; Lens et al, ; Markesteijn, Poorter, Paz, Sack, & Bongers, ; Zhang, Zhang, & Cao, ), a meta‐analysis of diverse species across a global dataset suggests that the trade‐off between these two traits is significant but weak (Gleason et al, ). Another important facet of xylem structure and function is a proposed trait trade‐off between storage and biomechanical strength and support (McCulloh et al, ; Scholz et al, ).…”
Section: Introductionmentioning
confidence: 99%